2009
DOI: 10.1037/a0017731
|View full text |Cite
|
Sign up to set email alerts
|

Working memory and aging: Separating the effects of content and context.

Abstract: In three experiments, we investigated the hypothesis that age-related differences in working memory might be due to the inability to bind content with context. Participants were required to find a repeating stimulus within a single series (no context memory required) or within multiple series (necessitating memory for context). Response time and accuracy were examined in two task domains: verbal and visuospatial. Binding content with context led to longer processing time and poorer accuracy in both age groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…The difficulty in obtaining evidence for an agerelated binding deficit for colour-shape conjunctions stands in stark contrast to the ubiquity of the associative deficit in memory for relations between items (Chen & Naveh-Benjamin, 2012;Old & Naveh-Benjamin, 2008a) in VWM (Cowan et al, 2006;Mitchell, Johnson, Raye, Mather, & D'Esposito, 2000;Peich et al, 2013), although this has proven less consistent (Bopp & Verhaeghen, 2009;Olson et al, 2004;Pertzov et al, 2015). In attempting to explain this disparity it is useful to draw a distinction between binding features within items, where the features define the intrinsic characteristics of an object, and retaining pairings of distinct items or contextual features accompanying an item, where the binding is between extrinsic features.…”
Section: Discussionmentioning
confidence: 73%
“…The difficulty in obtaining evidence for an agerelated binding deficit for colour-shape conjunctions stands in stark contrast to the ubiquity of the associative deficit in memory for relations between items (Chen & Naveh-Benjamin, 2012;Old & Naveh-Benjamin, 2008a) in VWM (Cowan et al, 2006;Mitchell, Johnson, Raye, Mather, & D'Esposito, 2000;Peich et al, 2013), although this has proven less consistent (Bopp & Verhaeghen, 2009;Olson et al, 2004;Pertzov et al, 2015). In attempting to explain this disparity it is useful to draw a distinction between binding features within items, where the features define the intrinsic characteristics of an object, and retaining pairings of distinct items or contextual features accompanying an item, where the binding is between extrinsic features.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have shown that older adults’ performance in a variety of working memory tasks is poorer than younger adults’ (Bopp & Verhaeghen, 2009; Brockmole et al, 2008; Cowan et al, 2006; Mitchell et al, 2000; Parra, Abrahams, Logie, et al, 2009; Sander et al, 2011a). These studies have mostly attributed the deficit to a decrease in the number of objects that can be held in memory.…”
Section: Discussionmentioning
confidence: 93%
“…In such blocking, the associative test no longer blends into the study events in comparison to the more salient item tests, which spatially look very different; in the associative block, the associative tests have only the study events with which to contrast. Of note, one commonality among experiments that do not find an associative deficit in working memory is that they all use a blocked test design, where the item test and associative test events are not intermixed (Bopp & Verhaeghen, 2009;Brockmole et al, 2008). Therefore, to investigate whether the associative deficit in older adults found in Experiment 1 in the short-term retention interval was due to the differential salience of tiie test events, we blocked tiie test type in Experiment 2 in addition to having a mixed test condition.…”
Section: Methodsmentioning
confidence: 98%